Work task and job satisfaction predicting low back pain among secondary school teachers in Putrajaya - Mohd Anuar, Nur Farahwahida; Rasdi, Irniza; M. Saliluddin, Suhainizam; Zainal Abidin, Emilia (Tehran University of Medical Sciences, 2016)
Background: : This study aimed to quantify the prevalence of low back pain (LBP), analyze its associated risk factors and explore on how LBP affects job satisfaction among 120 school teachers in Malaysia.